Self-reported Vocal symptoms among speech language pathologists dealing with children with hearing impairment and cerebral palsy - Kanwal, Shamsa; Mumtaz, Nazia (Journal of the Pakistan Medical Association, 2023)
A cross-sectional study was conducted at the Ripah International University, Lahore, Pakistan from January to April, 2022 to evaluate and compare the Self-Reported Vocal symptoms among Speech Language Pathologists (SLP) practicing with children having Hearing Impairment (HI) and Cerebral Palsy (CP). The sample included 141 participants of both genders, aged 25 to 60 years, practicing with children with hearing impairment and cerebral palsy for at least one year. Vocal Tract Discomfort Scale (VTDS) and Voice Activity Participation Profile (VAPP) were utilised for data collection which was analysed using SPSS Ver-23. The study revealed no significant association of self-perceived vocal symptoms for SLPs catering to CP and HI children with p=0.303 and p=0.412 for VTDS and VAPP scores respectively and with higher mean scores for SLPs catering to CP children. Results revealed a total VTDS score of 40.26±13.10 with highest score for dryness, while highest VAPP mean score was noted for daily communication (53.82±23.20). Hence, there is no significant association of the speciality being catered to, while dryness is the commonest self-perceived symptom. Keywords: Cerebral Palsy, Hearing Impairment, Self-concept, Speech-Language Pathologist.